PENGEMBANGAN PETA DIGITAL BERBANTUAN KOMPUTER BAGI MAHASISWA UAD PADA MATA KULIAH MATERI PEMBELAJARAN IPS - Dholina Inang Pambudi (Universitas PGRI Yogyakarta, 2016)
Research and development objectives are to: (1) Produce a map ditigal computer-aided development for students in courses Learning Materials Social Sciences (IPS) on student PGSD particularly mineral and mining of natural resources in the DIY (2). Determine the feasibility of products developed from the aspect of materials and media, as well as aspects of the student. This research is the subject of research and development consists of one expert material, one media expert, the trial is limited to half of the students PGSD UAD 3. Data collection instrument in the form of sheet material validation to experts and media experts, questionnaire for students. The acquired data is processed and analyzed using descriptive statistics as the material for the revision of the product to be eligible to use for testing in the field so that later can be used as a viable media used for students who follow courses Learning Materials IPS particularly mineral and mining of natural resources in DIY.Hasil of This is a research and development; computer-aided digital map media considered feasible to use as a tool in the learning process based on the assessment of expert judgment matter experts, media experts, and limited testing at PGSD students FKIP UAD. Based on the assessment criteria of material experts are included in the category of